The effect of mach drills training on the start movement of in-line speed skating - Liang, J. M.; Chen, J.; Sheu, S. T.; Lin, H. T.; Wu, W. L. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to analyze the relative muscle activation of the start movement and the Mach Drills training program. 5 in-line skating players participated in the study and 9 Wireless EMG sensors were placed over the rectus femoris, biceps femoris, semitendinosus, tibialis anterior, gastrocnemius, peroneus longus, adductor magnus, tensor fascia lata, and gluteus maximus. Results showed that significantly lower gastrocnemius IEMG value in skating. However, it also showed that RF, TA, and PL had higher IEMG value in skating and significant difference was found for TA. Another muscle activation didn`t have significantly difference. It suggested that athletes had to increase more specific training program for rectus femoris muscle and peroneus longus muscle which play an important roles for start movement in skating.